Enhancement of physical properties of electroactive polyimide nanocomposites by addition of graphene nanosheets. Issue 6 (12th September 2013) - Chang, Kung‐Chin; Lu, Hsin‐I; Lai, Mei‐Chun; Hsu, Chien‐Hua; Hsiao, You‐Rong; Huang, Kuan‐Yeh; Chuang, Tsao‐Li; Yeh, Jui‐Ming; Liu, Wei‐Ren
<x xml:space="preserve">Abstract</x> Electroactive polyimide/graphene nanocomposite (EPGN) membranes that consisted of EPI and carboxyl‐graphene nanosheets were found to exhibit enhanced physical properties as compared to the NEPI and EPI membranes. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>